Shifting Ethnographic Paradigms and Practices: Unleashing From Colonialism - Rai, Indra Mani (Journal of Education and Research, 2015)
This paper demonstrates realist ethnographic paradigms and practices of engaging an extended period of time to collect the information of distinctive socio-cultural structures or institutions of alien tribal or indigenous societies and describing their cultural ways of life patterns in positivistic manner detaching them from the research process. It argues that the interpretive or hermeneutic wave of ethnography deconstructs this Western hegemonic research tradition giving birth to the interpretation of socio-cultural world of the researched attaching meaning to what they say and do. It further argues that the emergence of critical reflexive ethnographic tradition is the dramatic shift that challenges the colonial ethnographic practices giving space to the self as reflexive research participant.  It helps to contest the colonial assumptions of structured and objective visualization of the world and authoritative representation of the other. The ethnographic tradition is further shifting towards promoting epistemic pluralism under postmodern ideologies employing multiple logics and genres to represent the self and the other. Auto/ethnography that embodies the postmodern notions facilitates the researchers to release from the cage of colonialism serving to adopt multiple ways of knowing indigenously being self-reflexive participants in the research process.